Effect of service quality on students satisfaction in private universities - M. Allo, Yusuf Rombe; Malau, Melinda (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study aimed to determine the effect of service, reliability, responsiveness, empathy, assurance, and tangibles in increasing student satisfaction at private universities in the LLDikti-3 region. The data collection method employed a qualitative approach, involving the use of questionnaires to gather responses. Qualitative data was transformed into quantitative data using a Likert scale. In this study, data collection was carried out directly from the number of students at the Universitas Kristen Indonesia. Universitas Sahid and Universitas Tarumanegara. The methods were used: Library Reseatch and. Field Research: This method conducts research by conducting direct surveys to be object to be studied of three private universities in the LLDIKTI-3 region. The data analysis technique in this research is multiple linear regression analysis, where this analysis is used to determine how much influence the change in a variable jas on other variables. In this study where the independent variables are reliability, responsiveness, empathy, assurance, and tangible, and the dependent variable. The results of the study stated that the quality of service provided by the three private universities in the LLDIKTI-3 region has a significant influence on student satisfaction. Dimensions of service quality play an important role in shaping student perceptions of university services.